ECONOMIC - INNOVATIVE THINKING AND THEIR DYNAMIC CHARACTERISTICS (TAMADDUN NURI JURNALI, 2024)
In this article, the dynamic features of socio-economic relations encourage business entities and entrepreneurs to develop new products, constantly expand the range of services, fully satisfy the needs of the population, and economic and innovative development is a product of relying on human thinking and potential, and its effective use. will be considered.